Listeria monocytogenes Monographic Study - Emil Tirziu; Ileana Nichita; Ciceronis Cumpanasoiu; Radu Valentin Gros; Monica Seres (Scientific Papers Animal Science and Biotechnologies, 2023)
Listeria monocytogenes is a ubiquitous bacteria with a remarkable resistance in discordant condition which produce listeriosis, an infectious disease that affects multiple domestic and wild animals’ species, but also humans. Receptive to listeriosis are the majority of domestic or wild mammals and birds, in the last years being registered an increase of receptivity in humans. The concept of listeriosis in human pathology, a disease caused by eating or drinking contaminated food and water, appeared for the first time in 1981, during an outbreak in Canada with seven cases in adults and 34 cases of maternal-fetal listeriosis. The alimentary origin of human listeriosis can be easily explained if considered some general characteristics of the bacteria. Thus, resistance in various conditions, especially at lower temperatures, justifies its dissemination and food contamination, particularly when is conserved by refrigeration. Also, L. monocytogenes has a significant presence in alimentary products. Some studies showed that 4% of the milk products, 29% of the meat products, 5% of the vegetable products and 26% of the products obtained from fishes and shell fishes are positive for L. monocytogenes, which allows us to say that battle against these bacteria is a war against microbial contamination.